2014
DOI: 10.1097/qad.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell and T-cell subset distributions and activation influence susceptibility to perinatal HIV-1 infection

Abstract: Objective To determine neonatal immunologic factors that correlate with mother-to-child-transmission of HIV-1. Design This case–control study compared cord blood natural killer (NK) and T-cell populations of HIV-1 exposed infants who subsequently acquired infection by 1 month (cases) to those who remained uninfected by 1 year of life (controls). Control specimens were selected by proportional match on maternal viral load. Methods Cryopreserved cord blood mononuclear cells (CBMCs) were thawed and stained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Under homeostatic condition and in the absence of other viral infections, this population of CD56 neg NK cells is either not detectable or present at very low frequency [2129]. The distribution and activation of NK cell subsets is relevant also in the context of mother-to-child HIV-1 transmission as they influence the susceptibility to perinatal infection [30]. …”
Section: Nk Cells and Hiv-1 Pathogenesismentioning
confidence: 99%
“…Under homeostatic condition and in the absence of other viral infections, this population of CD56 neg NK cells is either not detectable or present at very low frequency [2129]. The distribution and activation of NK cell subsets is relevant also in the context of mother-to-child HIV-1 transmission as they influence the susceptibility to perinatal infection [30]. …”
Section: Nk Cells and Hiv-1 Pathogenesismentioning
confidence: 99%
“…Taken together, these result in a more permissive state for the development of infections [ 1 ]. Many observational studies reported immunological abnormalities in HEU infants [ 14 ] including highly differentiated T-cell [ 15 ] and B-cell subsets [ 16 ], altered responses to vaccines [ 17 ], functional impairment of natural killer cells [ 18 ], and monocytes [ 19 ]. Furthermore, few studies considered early transmission of immunomodulatory human herpes virus (HHV), cytomegalovirus (CMV) [ 20 ], and/or Epstein-Barr virus (EBV) [ 21 ] recrudescence during pregnancy, because HHVs are important drivers of inflammation in HEU infants [ 20 ].…”
mentioning
confidence: 99%
“…Together these result in a more permissive state for the development of infections 1 . Many observational studies have reported immunological abnormalities in HEU infants 22 including highly differentiated T-cells [23][24][25][26][27][28][29] and B-cell subsets 30 , altered responses to vaccines [31][32][33] , functional impairment of natural killer cells 34 and monocytes [35][36][37] . Furthermore, few studies have considered early transmission of immunomodulatory human herpes virus' (HHVs), cytomegalovirus (CMV) 38 and Epstein Barr virus (EBV) 39 recrudescence during pregnancy on HEU immunity.…”
Section: Introductionmentioning
confidence: 99%